1996
DOI: 10.1111/j.1349-7006.1996.tb00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between Family History and Gastric Carcinoma among Young Adults

Abstract: The relationship between family history of gastric carcinoma and gastric carcinoma in Japanese under 40 years of age was analyzed. The subjects were 108 gastric carcinoma patients (86% were diffuse type) at 9 hospitals in the Kanto area of Japan. Firstly, incidence of gastric carcinoma among the parents of the subjects were compared with that in the general population. Observed/expected (O/E) ratios (P‐value) were 1.8 (0.06) for all subjects, 1.3 (0.62) for male subjects, 2.1 (0.04) for female subjects, 0.5 (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 10 publications
3
16
0
Order By: Relevance
“…The increased risk was not altered after multivariate adjustment for known or suspected risk factors of the disease. This result is consistent with the previous results of case-control, [11][12][13][14][15] cross-sectional 16,22,23 and prospective studies. 9 Our study more clearly demonstrated that the effect of family history varies in relation to the age and gender of the study participants and the type of affected relatives.…”
Section: Family History and Stomach Cancersupporting
confidence: 93%
“…The increased risk was not altered after multivariate adjustment for known or suspected risk factors of the disease. This result is consistent with the previous results of case-control, [11][12][13][14][15] cross-sectional 16,22,23 and prospective studies. 9 Our study more clearly demonstrated that the effect of family history varies in relation to the age and gender of the study participants and the type of affected relatives.…”
Section: Family History and Stomach Cancersupporting
confidence: 93%
“…Some studies found that a family history of stomach cancer was a stronger risk factor for women, 8,12,22,25 although the evidence is not consistent. 16 In some, 7,16,24 but not all 4,9,14 studies, the risk was higher for subjects with an affected sibling rather than a parent.…”
mentioning
confidence: 95%
“…Most research has been conducted in eastern Asian, 4,[8][9][10]12,13,18,[21][22][23] North American or in northern European countries, 2,5-7,11,15 but scanty information is available from Mediterranean countries. 14,20,24 The familial predisposition to stomach cancer, however, may have different genetic and environmental correlates in different populations, including a different prevalence of various susceptibility genes, and the impact of various environmental factors.…”
Section: 14mentioning
confidence: 99%
“…Gastric cancer results from a combination of environmental factors and accumulation of specific genetic alterations. In conventional gastric cancer (presenting >45 years old), environmental factors play a more important role, compared to early onset gastric cancer (EOGC, presenting at ≤45 years old) where it is postulated that genetic factors may be more important [20]. We have previously shown that molecular differences exist between conventional gastric cancer and EOGC [4][5][6][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%